2007
DOI: 10.1111/j.1365-313x.2007.03364.x
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species mediate Na+‐inducedSOS1mRNA stability in Arabidopsis

Abstract: SummarySalt Overly Sensitive 1 (SOS1), a plasma membrane Na + /H + antiporter in Arabidopsis, is a salt tolerance determinant crucial for the maintenance of ion homeostasis in saline stress conditions. SOS1 mRNA is unstable at normal growth conditions, but its stability is substantially increased under salt stress and other ionic and dehydration stresses. In addition, H 2 O 2 treatment increases the stability of SOS1 mRNA. SOS1 mRNA is inherently unstable and rapidly degraded with a half-life of approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
158
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(168 citation statements)
references
References 65 publications
(105 reference statements)
8
158
0
Order By: Relevance
“…1C). Similar posttranscriptional stabilization has been observed previously in salt stressregulated genes such as PEPCase (Cushman et al, 1990), AtP5R (Hua et al, 2001), and SOS1 (Shi et al, 2003;Chung et al, 2008) and in abscisic acid-and water stress-regulated genes such as a-amylase/subtilisin inhibitor (BASI; Liu and Hill, 1995), le25, and his1-s (Cohen et al, 1999). Taken together, our results suggest that the SMD of RbcS1 and Cab1 as well as the control of the stress-inducible Dip1 and SalT genes are posttranscriptional events.…”
Section: Smd Of Photosynthetic Genes During Stress Conditionssupporting
confidence: 70%
“…1C). Similar posttranscriptional stabilization has been observed previously in salt stressregulated genes such as PEPCase (Cushman et al, 1990), AtP5R (Hua et al, 2001), and SOS1 (Shi et al, 2003;Chung et al, 2008) and in abscisic acid-and water stress-regulated genes such as a-amylase/subtilisin inhibitor (BASI; Liu and Hill, 1995), le25, and his1-s (Cohen et al, 1999). Taken together, our results suggest that the SMD of RbcS1 and Cab1 as well as the control of the stress-inducible Dip1 and SalT genes are posttranscriptional events.…”
Section: Smd Of Photosynthetic Genes During Stress Conditionssupporting
confidence: 70%
“…SOS1, a Na + / H + antiporter, which is a target of the SOS3/SOS2 complex, has been reported to be posttranscriptionally regulated by ROS and to interact with oxidative responses regulators (Katiyar-Agarwal et al, 2006;Chung et al, 2008). In rice cultured cells treated with PAMPs, CIPK14/15 appear to mediate ROS production (Kurusu et al, 2010), and, more recently, Arabidopsis CIPK26 was shown to interact with RBOHF in planta and positively and negatively regulate its ROS-producing activity in human cultured cells (HEK293T) (Kimura et al, 2012;Drerup et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative mode by which H 2 O 2 and probably other ROS mediate abiotic stress responses is stabilization of specific transcripts that encode stress-related proteins. Chung et al (2008) demonstrated that increased ROS levels enhance the stability of the saltinduced SOS1 mRNA. This plasma membrane Na 1 / H 1 antiporter interacts via its cytoplasmic tail domain with runaway cell death 1, revealing a new function for SOS1 within the oxidative stress response (KatiyarAgarwal et al, 2006).…”
Section: Ros In Abiotic Stress Responsesmentioning
confidence: 99%